Let f(x) = 2- x^2 and g(x) = x^2 -2. How do you solve f(x) = g(x) ? Algebra Graphs of Linear Equations and Functions Function Notation and Linear Functions 1 Answer Harold Walden Sep 29, 2015 x=+-sqrt(2) Explanation: If f(x)=g(x) then 2-x^2=x^2-2 and 4=2x^2 2=x^2 Therefore, x=sqrt(2), x=-sqrt(2) Hope this helps :) Answer link Related questions What is an example of a linear equation written in function notation? What is a function? How do you evaluate f(4) given the function f(x)=2x-6? How do you evaluate g(-1) given the function g(t)=-5t+1? How do you write linear equations in function notation? How do you rewrite 9x+3y=6 in function notation? How do you evaluate f(p) given the function f(x)=6x-36? What are linear functions? How do you evaluate f(0) given the function f(x)=\frac{5(2-x)}{11}? How do you evaluate f(-1) given the function f(t)=\frac{1}{2} t^2+4? See all questions in Function Notation and Linear Functions Impact of this question 2375 views around the world You can reuse this answer Creative Commons License